2004
DOI: 10.4314/sajas.v33i4.3777
|View full text |Cite
|
Sign up to set email alerts
|

Revised models and genetic parameter estimates for production and reproduction traits in the Elsenburg Dormer sheep stud

Abstract: Genetic parameters for production and reproduction traits in the Elsenburg Dormer sheep stud were estimated using records of 11743 lambs born between 1943 and 2002. An animal model with direct and maternal additive, maternal permanent and temporary environmental effects was fitted for traits considered traits of the lamb (birth and weaning weight and survival). Fixed effects were sex, birth status, year and age of dam. Weaning weights were pre-adjusted to a 100-day equivalent. For reproduction traits (consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
11
19
1
1
Order By: Relevance
“…Mokhtari et al (2010) reported that the direct heritability for this trait was 0.18 which was the same value as calculated in the present research. This estimate was in the range of 0.03-0.4 as reported by several authors (Rosati et al 2002;van Wyk et al 2003;Mohamadi et al 2012;Amou Posht-e-Masari et al 2013;Mohammadabadi and Sattayimokhtari 2013). The heritability of TLWW was higher than of the other traits, which may be due to genetic variation in this trait according to the increase in the weaning weight of lambs (Mokhtari et al 2010;Rashidi et al 2011).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Mokhtari et al (2010) reported that the direct heritability for this trait was 0.18 which was the same value as calculated in the present research. This estimate was in the range of 0.03-0.4 as reported by several authors (Rosati et al 2002;van Wyk et al 2003;Mohamadi et al 2012;Amou Posht-e-Masari et al 2013;Mohammadabadi and Sattayimokhtari 2013). The heritability of TLWW was higher than of the other traits, which may be due to genetic variation in this trait according to the increase in the weaning weight of lambs (Mokhtari et al 2010;Rashidi et al 2011).…”
Section: Resultssupporting
confidence: 78%
“…Heritability estimate for this trait varied from 0.01 to 0.189 (Bromley et al 2001;Rosati et al 2002;van Wyk et al 2003;Vanimisetti et al 2007;Ceyhan et al 2008;Amou Posht-e-Masari et al 2013). Lower heritability for LSW, compared with the heritability estimate for LSB, suggested that the loss of lambs from birth to weaning is influenced mainly by environmental factors such as a particular disease and mortality of lambs.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of these software packages enabled researchers to partition the respective random effects for various livestock species and breeds (Meyer, 1992;1994;Olivier et al, 1994;Purvis, 1995;Swan et al, 1995;Snyman et al, 1995;Meyer, 1997). In addition, Van Wyk et al (2003) and Safari et al (2007b) partitioned the dam environmental variance into a temporary litter effect and a permanent environmental effect (the correspondence of records of the same dam across breeding seasons) to accurately reflect the contribution of the respective components. Furthermore, Asadi Fozi et al (2005) reported the importance of including maternal genetic effects for fleece traits in Merino breeding programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated direct additive heritability for TWLB/EL in this study (0.08) is consistent with the value of heritability reported for this trait by Fogarty (1995). The range of direct additive heritability for TWLB/EL was reported 0.04 to 0.4 by Matika, Van Wyk, Erasmus, andBaker (2003) andvanWyk et al (2003). TWLB/EL is a combination of the number of lambs born and the weight of lambs in each birth of ewe and indicates the ewe's capacity to produce kg weight of lamb without considering the number of lambs .…”
Section: Resultsmentioning
confidence: 99%